A novel GaN MIS‐HEMT with a floating clamp electrode for suppressing short‐channel effect. Issue 19 (3rd July 2021) - Shi, Yijun; Wang, Hongyue
Abstract: In this work, a novel GaN MIS‐HEMT (metal‐insulator‐semiconductor high electron mobility transistors) featuring a floating clamp (FC) electrode is proposed for suppressing the short‐channel effect. By inserting the FC electrode near to the drain‐side gate edge, the transverse potential at the gate edge can be clamped to less than 2 V, thereby the short‐channel effect can be suppressed. Compared to the conventional short‐channel GaN MIS‐HEMT, the proposed device exhibits much decreased off‐state electron density at the drain voltage of 10 V, which leads to the off‐state leakage current decreasing from 10 –1 to 10 –7 A/mm, without an obvious sacrifice of the on‐state current. Meanwhile, the proposed GaN MIS‐HEMT also delivers a much lower reverse gate‐to‐drain capacitor. The excellent characteristics of the proposed GaN MIS‐HEMT show that the device is promising for the future power applications.